A peptide inhibitor of antibody-dependent cell-mediated cytotoxicity against EGFR/folate receptor-α double positive cells. Issue 5 (8th March 2018) - Sasaki, Koichi; Miyashita, Yoshiki; Asai, Daisuke; Funamoto, Daiki; Sato, Kazuki; Yamaguchi, Yoko; Mishima, Yuji; Iino, Tadafumi; Takaishi, Shigeo; Nagano, Jun; Kishimura, Akihiro; Mori, Takeshi; et al.
Abstract : ADCC is caused by NK cells upon recognition of antigen-bound IgG via FcγRIIIa. Abstract : Antibody-dependent cell-mediated cytotoxicity (ADCC) is caused by natural killer (NK) cells upon recognition of antigen-bound IgG via FcγRIIIa. This mechanism is crucial for cytolysis of pathogen-infected cells and monoclonal antibody (mAb)-mediated elimination of cancer cells. However, there is concern that mAb-based cancer therapy induces ADCC against non-target cells expressing antigens. To date, no strategy has been reported to enhance the selectivity of ADCC to protect non-target cells expressing antigens. Here, we introduce a model inhibitor which specifically blocks ADCC of anti-EGFR mAbs towards EGFR/folate receptor α (FRα) double positive cells. This inhibitor recruits mAbs on the FRα of the cell surface independent of Fab antigen recognition. The resulting ternary and/or quaternary complexes formed on the cell surface suppress signal transduction of FcγRIIIa in NK cells, consequently leading to more specific ADCC.